The effect of equal-channel angular pressing (ECAP) on the properties of graphene reinforced aluminium matrix composites - Guler, Omer; Bagci, Nihal; Guler, Seval Hale; Canbay, Canan A.; Safa, Hasan; Yilmaz, Taha A.; Taskin, Mustafa (Sage Publications Ltd, 2021)
In the present study, graphene nanosheets were synthesised by liquid phase exfoliation process, and the obtained graphene was reinforced in the rates of 0.1, 0.2, 0.3 and 0.6 wt.%. After the composites were characterised, they were exposed to Equal Channel Angular Pressing (ECAP) process. While 0.1 wt.% and 0.2 wt.% graphene reinforced composite samples successfully completed the ECAP process, 0.1 wt.% and 0.2 wt.% graphene reinforced composite samples were broken during the ECAP process. Electrical, thermal, and mechanical properties of the composite increased with the increased amount of graphene. The mechanical properties of ECAP-processed samples showed significant increases compared to non-ECAP processed samples. To figure out the effect of the ECAP process, moulds with different channel angles were used, the ECAP temperature was changed, and different passes were performed and the angles of 120 degrees and 90 degrees were used. ECAP-processed samples in both mould angles showed similar mechanical properties. With the increasing ECAP temperature, the mechanical properties of the sample decreased, but its electrical conductivity increased. As the number of passes increased, mechanical properties increased and crack formation in material increased. In addition, it was not possible to successfully remove the matrix composites containing more than 0.3 wt.% graphene from the ECAP process. Especially in the sample containing 0.6 wt.% graphene, brittle fractures were seen during the ECAP process and the sample was divided into many parts. The results showed that the composite responded better to the ECAP process when low amounts of graphene were reinforced in the al matrix. Significant improvements were observed in the properties of these composites after the ECAP process. In this study, the properties of composites with and without ECAP process were extensively investigated. The results were compared in detail with the previous studies. The graphene was produced using a simple method and it was reinforced with the Al matrix with the easiest possible method.
Keywords: Graphite; graphene; exfoliation; aluminium; powder metallurgy; equal channel angular pressing (ECAP)